Attitude and Performance of Health Staff Regarding Health Information Resources Kerman University of Medical Sciences - Azadeh Sadeghi; Fatemeh Balali; Sadollah Razazade (Journal of Education and Community Health)
Introduction: Using different media and information resources in the field of health is to achieve three key outcomes as learning correct health information, change in attitudes related to health and creating new healthy behaviors. This study was performed to determine the attitudes and performance of staff regarding health information resources in health centers of Kerman University of Medical Sciences. Materials and Methods: In this cross-sectional study, all health personnel working in Kerman University of Medical Sciences were evaluated during 2012-13 (N=223). Data collection tool was a researcher made questionnaire containing demographic characteristics, attitudes, and practices questionnaire (α=0.9). Scores of attitude and practice were categorized into three levels as low (under 50%), moderate (50-75%) and good (over 75%). The data was analyzed using SPSS-20 statistical software by Chi-square and Pearson correlation. Results: In total, 42.6% of the study population had a positive attitude and 61.9% had a poor performance score. There was a positive correlation between attitude and practice scores (P<0.001). There was no significant association between attitude and practice scales with gender, age and work experience (P>0.05). Conclusion: Attitude of most study population regarding health information resources was in moderate level and their performance was weak. Therefore, it is suggested to design and implement educational interventions for more efficient use of health information resources among staff.